2011
DOI: 10.1097/prs.0b013e318221db4d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperhomocysteinemia on the Microcirculation of Skin Flaps

Abstract: The authors demonstrated, for the first time, that hyperhomocysteinemia severely suppressed the microvasculature of skin flaps, as shown by increased flap necrosis and reduced microvessel calibration in the experimental group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In the present study, the plasma total homocysteine level was increased following ingestion of 1% methionine diet, which confirms previous data demonstrating that hyperhomocysteinemia could be induced by a high methionine diet [5, 6]. No difference seen in the mean total food intake in all groups suggests that the intake of methionine in all groups except in the control group was similar.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the plasma total homocysteine level was increased following ingestion of 1% methionine diet, which confirms previous data demonstrating that hyperhomocysteinemia could be induced by a high methionine diet [5, 6]. No difference seen in the mean total food intake in all groups suggests that the intake of methionine in all groups except in the control group was similar.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have shown that hyperhomocysteinemia can be induced by feeding experimental animals with a high methionine diet [5, 6]. Hyperhomocysteinemia enhances production of a reactive oxygen species (ROS), leading to increased oxidative stress [7] which then reduces nitric oxide (NO) production [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hyperhomocysteinemia is associated with microvascular failure. ( 27 ) Hcy can be methylated to form methionine, catalyzed by the enzyme methionine synthase and folic acid and vitamin B 12 cofactors. ( 28 ) The conversion of Hcy to cystathionine is catalyzed by systathionine β-synthase in the liver.…”
Section: Discussionmentioning
confidence: 99%